DNA barcoding of threatened fishes of Bangladesh: DNA barcoding of threatened fishes of Bangladesh - Hossain, Zarif; Sanzida, Nusrat Jahan; Akhand, Md Anwarul Azim; Ahmed, Md Sagir (Bioresearch Communications, 2021)
The ichthyofaunal diversity of Bangladesh is declining dramatically due to various anthropogenic factors. For authentic identification at species level, approximately 655 bp of the mitochondrial cytochrome c oxidase subunit I (COI) gene of 29 threatened fish species were amplified and a barcode dataset was generated. Among these species, 7% were categorized as Critically Endangered (CR), whereas 55% and 38% were categorized as Endangered (EN) and Vulnerable (VU), respectively. K2P genetic distances were evaluated and found to be increasing with higher taxonomic rank—1.01% to 13.09% within species and 17.42% to 41.57% between species with a DNA barcode gap of 4.33%. The average %GC content of the fish species was 44.7 ± 0.49. On the other hand, the %GC values for the 6 orders—Cypriniformes, Siluriformes, Synbranchiformes, Syngnathiformes, Perciformes and Osteoglossiformes were 44.8 ± 0.81, 45.6 ± 0.61, 44.8 ± 0.85, 47 ± 0.99, 46.3 ± 0.89, 47 ± 0.90, respectively. The %GC content was highest in the first codon followed by the second and third codons for both the individual species and the Orders (1st>2nd>3rd). It was also observed that the most synonymous mutations occur at the 3rd codon position followed by the 1st and the 2nd codons. Finally, genetic variations were identified in Raiamas bola (at position 101), Ompok bimaculatus (at position 396) and Cirrhinus reba (at positions 108, 273, 310, 345, 420, 462, 495, 540 and 591) including 3 incidents of transversion (A instead of C). Thus, two different groups of C. reba emerged in the phylogram. This study, for the first time, focuses on COI based molecular characterization of the threatened fish species of Bangladesh and therefore, might work as a referral study for their authentic identification and in-situ conservation. Bioresearch Commu. 7(2): 990-998, 2021 (June)